Alcohol abuse and cigarette smoking are associated with global DNA hypermethylation: results from the German Investigation on Neurobiology in Alcoholism (GINA) - Semmler, Alexander; Heese, Peter; Stoffel-Wagner, Birgit; Muschler, Marc; Heberlein, Annemarie; Bigler, Laurent; Prost, Jean-Christophe; Frieling, Helge; Kornhuber, Johannes; Banger, Markus; Bleich, Stefan; Hillemacher, Thomas; et al. (Alcohol, 2015)
Recent studies have shown that smoking and alcoholism may be associated with altered DNA methylation and that alcohol consumption might induce changes in DNA methylation by altering homocysteine metabolism. In this monocenter study, we included 363 consecutive patients referred for hospitalization for alcohol detoxification treatment. Blood samples were obtained on treatment days 1, 3, and 7 for measurement of global DNA methylation in leukocytes by liquid chromatography tandem mass spectrometry. Genomic DNA was used for genotyping the following seven genetic variants of homocysteine metabolism: cystathionine beta-synthase (CBS) c.844_855ins68, dihydrofolate-reductase (DHFR) c.594 + 59del19bp, methylenetetrahydrofolate-reductase (MTHFR) c.677C > T and c.1298A > C, methyltetrahydrofolate-transferase (MTR) c.2756A > G, reduced folate carrier 1 (RFC1) c.80G > A, and transcobalamin 2 c.776C > G. Multivariate linear regression showed a positive correlation of global DNA methylation with alcohol consumption and smoking on day 1 of hospitalization. DNA methylation was not correlated with homocysteine or vitamin plasma levels, nor with the tested genetic variants of homocysteine metabolism. This suggests a direct effect of alcohol consumption and smoking on DNA methylation, which is not mediated by effects of alcohol on homocysteine metabolism.
EVALuna2:23732